DI-011 Pharmacist's role on adherence and literacy in a cancer outpatient setting. (24th March 2015) - Ribed, A; Romero-Jiménez, RM; Escudero-Vilaplana, V; Buendía-Bravo, S; Monje García, B; Tovar Pozo, M; Osorio, S; Herranz-Alonso, A; Codina, C; Sanjurjo Sáez, M
Abstract : Background: Oral anticancer agents (OAAs) require self-administration by patients at home, increasing the risk of non-adherence and consequently, costs and decreasing overall patient survival. Purpose: To assess the impact of a comprehensive pharmaceutical care service on oncology outpatients' adherence. Secondary objectives were to analyse influencing factors and to compare different adherence tests. Material and methods: A comprehensive care program was developed in 2012. Pharmacist interviews and literacy reinforcement took place at the beginning of the treatment, after one and six months. A pre-post study was conducted. Patients starting treatment with OAAs in 2011 formed the control group and the ones who started in 2013, the intervention group. Demographics, tumour, OAA, current drug treatment, adherence evaluated by dispensing records and by Morisky-Green and Haynes-Sackett test data were collected at every visit. A patient was considered adherent when reaching 90% adherence. Results: 115 patients formed the control group and 134 the intervention group (158 men and 91 women; mean age of 66.9). The most common diagnosis was lung cancer (26%). On average, patients were taking 5 drugs concurrently. The adherence rate in the first month was 94.7% in the control group and 95.7% in the intervention group (p > 0.05); after 6 months on treatment, it was 87.7% in the control group and 95.0% in the intervention group (p = 0.025). Moreover, the percentage of adherent patients increased in the intervention group after 6 months of treatment by 20% (60.5% vs. 80.8%, p = 0.001). In the intervention group, self-reported measurements depicted higher adherence rates that did not correlate with the record of prescriptions issued. Age and gender did not affect adherence. In contrast, differences were observed between OAAs (p = 0.008): sunitinib and pazopanib had the lowest rate of adherence (88.0%) in the first month and sorafenib (82.8%) in the 6th month. Conclusion: A comprehensive pharmaceutical care program improves adherence, resulting in a 20% increase in adherent patients after 6 months of treatment. Differences in adherence were observed between OAAs. References and/or acknowledgements: No conflict of interest.